Optimizing Farmer Managed Natural Regeneration Efforts Using Geospatial Technology - Kigen, Charles; Korir, Janet; Chesire, Michael; Munyao, Carol; Too, Prisca (International Journal of Environmental Sciences, 2025)
Farmer Managed Natural Regeneration (FMNR), holds immense potential for addressing land degradation and enhancing ecosystem services in the arid and semi-arid lands. However, decisions regarding where to prioritize FMNR efforts and effectively monitor adoption and impact require reliable data and objective analysis. Spatial technologies (ST) such as Remote Sensing (RS), Geographic Information Systems (GIS), and GPS play a crucial role in achieving these goals. This paper explores the application of ST in optimizing FMNR implementation in Kenya. It discusses how ST can be used to identify suitable areas for FMNR based on factors like land degradation severity, vegetation cover, and socio-economic characteristics. Additionally, the paper explores how ST can be utilized to monitor FMNR adoption by tracking changes in land cover over time and assess the impacts of FMNR on ecosystem services like carbon sequestration and biodiversity conservation. Finally, the paper highlights the challenges and opportunities associated with using ST for FMNR and proposes recommendations for its effective integration into FMNR programs.